No difference in frontal cortical activity during an executive functioning task after acute doses of aripiprazole and haloperidol - Bolstad, Ingeborg; Andreassen, Ole A.; Groote, Inge R.; Haatveit, Beathe; Server, Andres; Jensen, Jimmy (Frontiers in Human Neuroscience, 2015)
Background: Aripiprazole is an atypical antipsychotic drug that is characterized by partial dopamine D2 receptor agonism. Its pharmacodynamic profile is proposed to be beneficial in the treatment of cognitive impairment, which is prevalent in psychotic disorders. This study compared brain activation characteristics produced by aripiprazole with that of haloperidol, a typical D2 receptor antagonist, during a task targeting executive functioning. Methods: Healthy participants received an acute oral dose of haloperidol, aripiprazole or placebo before performing an executive functioning task while blood-oxygen-level-dependent (BOLD) functional magnetic resonance imaging (fMRI) was carried out. Results: There was a tendency towards reduced performance in the aripiprazole group compared to the two other groups. The image analysis yielded a strong task-related BOLD-fMRI response within each group. An uncorrected between-group analysis showed that aripiprazole challenge resulted in stronger activation in the frontal and temporal gyri and the putamen compared with haloperidol challenge, but after correcting for multiple testing there was no significant group difference. Conclusion: No significant group differences between aripiprazole and haloperidol in frontal cortical activation were obtained when corrected for multiple comparisons. This study is registered in ClinicalTrials.gov (identifier: 2009-016222-14; https://clinicaltrials.gov/).